Difficult-to-float lignite reverse flotation based on forced pre-mudding - LI Yunchang; XIA Yangchao; LI Ao; WANG Hao; BUDEEBAZAR Avid; XING Yaowen; GUI Xiahui (矿业科学学报, 2025)
Lignite is prone to mudding and poor separation effect in direct flotation. This study puts forward a lignite flotation method of forced mudding combined with reverse flotation for efficient ash reduction and quality improvement of difficult-to-float lignite. We investigated the patterns of forced mudding in lignite and its mechanism in promoting reverse flotation. The -0.045 mm size fraction lignite increased by 12.58% after a 30 min treatment to realize the forced dispersion and dissolution of the ash minerals. Flotation tests were carried out using 4 methods: conventional direct flotation, forced pre-mudding combined with direct flotation, conventional reverse flotation, and forced pre-mudding combined with reverse flotation. Results show that direct flotation after mudding treatment increased the yield of clean coal by 3.5% and reduced the ash content by 0.4% compared to flotation without mudding treatment. However, the clean coal yield only reached 20.44%, and the ash content was about 17%. Reverse flotation tests were carried out using the same consumption of reagents, the reverse flotation was more effective than the direct flotation process, with a clean coal yield of 60%, and the ash content as high as 14%. On this basis, the use of forced mudding pretreatment was found to increase the clean coal yield by 5.81% and reduce the ash content by 1% to 2% compared with direct reverse flotation, yielding a more considerable sorting index. The coarse-grained gangue and companions were fragmented after forced mudding, and the relative contents of Si and Al on the surface of +0.045 mm size fraction lignite decreased by 0.65% and 1.17%, respectively. This indicates that the forced mudding treatment could promote the dissolution and dispersion of gangue minerals and reduce the content of gangue minerals on the coal surface. It could reduce the adsorption of reverse flotation collector on the coal surface and strengthen its interaction with gangue minerals, thus improving the index of clean coal in reverse flotation.